Hot avulsion may be effective as salvage treatment for focal Barrett’s esophagus remaining after endoscopic therapy for dysplasia or early cancer: a preliminary study - Aranda-Hernández, Javier; Shimamura, Yuto; Grin, Andrea; Iwaya, Yugo; Cirocco, Maria; Kandel, Gabor; May, Gary; Kortan, Paul; Raftopoulos, Spiro; Marcon, Norman (Endoscopy, 2018)
Background and study aim Both endoscopic mucosal resection (EMR) and radiofrequency ablation (RFA) are used to treat Barrett’s esophagus (BE) complicated by dysplasia and intramucosal cancer. However, focal areas of BE can remain after otherwise successful application of these techniques. We report the results of hot avulsion using a hot biopsy forceps to resect these residual focal areas.Patients and methods This was a retrospective study from a prospective database in a tertiary reference center from August 2013 to May 2015. All included patients had undergone hot avulsion for eradication of residual focal areas of BE that were ≤ 1 cm and not suspicious for dysplasia, following at least one previous endoscopic treatment for dysplasia or intramucosal cancer. Results 35 patients harboring 124 residual areas of 1 – 7 mm were treated with hot avulsion. After a mean follow-up of 17.4 months, all patients achieved complete eradication of residual focal BE. One of the patients required a second hot avulsion treatment. Hot avulsion provided samples in all cases but limited the assessment of dysplasia (cautery artifact) in 20.2 % of them. The only complication was bleeding in two patients, which was easily stopped by soft coagulation.Conclusions Hot avulsion appears to be effective and safe in removing focal BE ≤ 1 cm at its greatest length remaining after endoscopic treatment for dysplasia or early cancer. Further studies are required before this technique can be considered the standard of care.